2013
DOI: 10.1371/journal.pone.0062570
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Injectable Calcium Phosphate Cement-Bioactive Glass Composite for Bone Regeneration

Abstract: BackgroundCalcium phosphate cement (CPC) can be molded or injected to form a scaffold in situ, which intimately conforms to complex bone defects. Bioactive glass (BG) is known for its unique ability to bond to living bone and promote bone growth. However, it was not until recently that literature was available regarding CPC-BG applied as an injectable graft. In this paper, we reported a novel injectable CPC-BG composite with improved properties caused by the incorporation of BG into CPC.Materials and MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 45 publications
6
75
0
Order By: Relevance
“…[ 10 ] Compressive strengths of hardened bioactive glass (a source of Si)-added CPC was increased compared to Si-free CPC. [ 3,6 ] In addition, Si-added CPC demonstrated improved in vitro and in vivo osteoconduction. [ 6,8 ] Another approach to formulate CPSC is to incorporate monocalcium phosphate (MCP) into calcium silicate cement (CSC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] Compressive strengths of hardened bioactive glass (a source of Si)-added CPC was increased compared to Si-free CPC. [ 3,6 ] In addition, Si-added CPC demonstrated improved in vitro and in vivo osteoconduction. [ 6,8 ] Another approach to formulate CPSC is to incorporate monocalcium phosphate (MCP) into calcium silicate cement (CSC).…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] A recent metaanalysis found that the use of bone cement can signifi cantly reduce pain after surgery and prevent further fractures. [ 4 ] The most common and clinically used calcium phosphate cement (CPC) is able to transform into hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) under physiological conditions, which forms an apatite layer at the tissue-implant interface and promotes osteogenic differentiation of marrow stromal cells into osteoblast cells. [ 5 ] However, CPC has been reported to insuffi ciently support bone reconstruction at poorly vascularized sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed there is increasing research in the field of injectable calcium phosphate cements with recent efforts focusing on incorporating different additives including inorganic bioactive elements, e.g. bioactive glass [55], radiopacifiers, e.g. tantalum oxide or barium sulfate [56], biodegradable polymers to improve the injectability [57]and modifications to incorporate antibiotic releasing capability [58].…”
Section: Osteoporosis a Materials Scientist's Point Of Viewmentioning
confidence: 99%
“…Besides hBMSCs and hUCMSCs, stem cells derived from dental tissues, such as dental pulp stem cells (DPSCs) and deciduous teeth stem cells (DTSCs) with the property to form a calcified matrix, also showed promising results for the regeneration of mineralized tissues in combination with CPCs (Xia et al, 2013). hucMsc AnD hbMsc sEEDing On cPc fOr bOnE rEgEnErAtiOn in vivo Strategies for the acceleration of bone regeneration via CPC include the addition of bioactive agents such as osteocalcin, O-phospho-L -serine (Vater et al, 2010), and bioactive glass (Yu et al, 2013). Another strategy for the enhancement of bone regeneration is to combine stem cells with CPC (Zeng et al, 2012;Zou et al, 2012;Chen et al, 2013a).…”
Section: Co-culturing Osteoblasts/endothelial Cells To Prevascularizementioning
confidence: 99%